Whom Should We Talk to? Investigating the Varying Roles of Internal and External Relationship Quality on Radical and Incremental Innovation Performance. Issue 6 (December 2016) - Obal, Michael; Kannan‐Narasimhan, Rangapriya; Ko, Guihan
Abstract : Research suggests that close relationships with internal and external partners are likely to have a significant impact on new product development (NPD). What is unclear is how the effects of internal and external relationships influence development paths for different types of innovations. Prior literature indicates that the pathways for developing incremental innovations differ considerably from those for radical innovations. Thus it is plausible that the effects of external versus internal relationships vary across these two innovation types. This paper uses the 2012 Comparative Performance Assessment Study (CPAS) data set to investigate the roles of internal and external relationship quality on the development of both incremental and radical innovations. The results find that internal and not external relationship quality is beneficial for the development of incremental innovations. When driven by internal relationships, a flexible NPD process is advantageous for the financial performance of incremental innovations. Meanwhile external and not internal relationship quality is valuable for developing radical innovations. External relationship quality results in process flexibility, leading to project execution success and subsequent financial performance for radical innovations. As expected, project execution success consistently leads to increased financial performance. These findings indicate the critical differences in types of relationship quality required when developing new products based on radical versus incremental innovations.